2023
DOI: 10.3390/vaccines11091455
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous COVID-19 Vaccination and Booster with mRNA Vaccine Provide Enhanced Immune Response in Patients with Cirrhosis: A Prospective Observational Study

Pimsiri Sripongpun,
Nawamin Pinpathomrat,
Ratchanon Sophonmanee
et al.

Abstract: This study aimed to evaluate the antibody and cellular responses to different coronavirus 2019 (COVID-19) vaccination regimens in patients with cirrhosis and to assess the antibody response after a vaccine booster. We conducted a prospective observational study of 89 patients with cirrhosis and 41 healthy volunteers who received two COVID-19 vaccine doses. Next, we prospectively evaluated 24 patients with cirrhosis who received a booster COVID-19 vaccine dose. In both studies, blood samples were collected befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(28 reference statements)
0
1
0
Order By: Relevance
“… 40 Another study observed higher immunogenicity of both humoral and cellular responses to the heterologous COVID-19 vaccine regimen compared to homogeneous regimens in patients with cirrhosis. 41 Therefore, we speculate that further booster doses of COVID-19 vaccination with heterologous regimens could possibly enhance the immune response of patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 96%
“… 40 Another study observed higher immunogenicity of both humoral and cellular responses to the heterologous COVID-19 vaccine regimen compared to homogeneous regimens in patients with cirrhosis. 41 Therefore, we speculate that further booster doses of COVID-19 vaccination with heterologous regimens could possibly enhance the immune response of patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 96%